2020
DOI: 10.1186/s13048-020-00622-x
|View full text |Cite
|
Sign up to set email alerts
|

Live birth rate comparison of three controlled ovarian stimulation protocols for in vitro fertilization-embryo transfer in patients with diminished ovarian reserve after endometrioma cystectomy: a retrospective study

Abstract: Background: Women with endometriosis and previous cystectomy may respond less well to gonadotropin stimulation, which results in fewer oocytes retrieved and poor pregnancy outcomes. Choosing an appropriate protocol for such populations is essential. This study involved an analysis of the effect of different controlled ovarian stimulation (COS) protocols on the clinical outcomes of in vitro fertilization-embryo transfer (IVF-ET) in women with diminished ovarian reserve (DOR) who underwent ovarian endometrioma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 46 publications
(40 reference statements)
4
34
0
1
Order By: Relevance
“…Also, these pregnancies were likely to be healthier reflected by lower abortion rate (28% vs 34% in antagonist cycles). 21 Similarly, in our study cohort we found a beta HCG positive rate (Implantation Rate) 33 % for agonist cycle as compared to 25% for antagonist cycle. Although we had no cycle cancellation, agonist protocol is likely to have more cycle cancellation as compared to antagonist cycle.…”
Section: Adjuvant To Treatmentsupporting
confidence: 71%
“…Also, these pregnancies were likely to be healthier reflected by lower abortion rate (28% vs 34% in antagonist cycles). 21 Similarly, in our study cohort we found a beta HCG positive rate (Implantation Rate) 33 % for agonist cycle as compared to 25% for antagonist cycle. Although we had no cycle cancellation, agonist protocol is likely to have more cycle cancellation as compared to antagonist cycle.…”
Section: Adjuvant To Treatmentsupporting
confidence: 71%
“…Pregnancies were diagnosed according to the serum B-hCG levels 14 days after embryo transfer and the clinical pregnancy was confirmed by visualization of a gestational sac on ultrasonographic examination 28 to 35 days after the embryo transfer. [ 13 ] The biochemical pregnancy was defined as the serum β-HCG > 25U/L 14 days after embryo transfer. Live birth was considered when a living fetus was born after 28 weeks of pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…We followed the routine ovarian hyperstimulation [18] and all female patients were injected daily at a fixed time with a subcutaneous follicle-stimulating hormone (Gn, Gonal-F, Merck Serono, USA) from the 3rd to the 5th day of the menstrual cycle.…”
Section: Clinical Manipulations 1 Controlled Ovarian Hyperstimulation...mentioning
confidence: 99%